2020
DOI: 10.1103/physrevc.102.064611
|View full text |Cite
|
Sign up to set email alerts
|

Reaction channel contributions to the triton optical potential

Abstract: Reaction channel contributions to the triton optical potential. Physical Review C, 102(6), article no. 064611.For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…In a study of the pickup contribution to the 3 H OMP for 33 MeV 3 H on 48 Ca, we found R CS = 0.55, Ref. [29]. For 33 MeV 3 He on 48 Ca, we found R CS = 0.71 [28].…”
Section: Regularities In R Csmentioning
confidence: 73%
“…In a study of the pickup contribution to the 3 H OMP for 33 MeV 3 H on 48 Ca, we found R CS = 0.55, Ref. [29]. For 33 MeV 3 He on 48 Ca, we found R CS = 0.71 [28].…”
Section: Regularities In R Csmentioning
confidence: 73%
“…The state CS is not necessarily equal to the change in reaction cross section (CS) and the relationship between the two can vary widely, Refs. [2,14,15], depending on the particular case. In cases where inelastic coupling is included together with reaction channel coupling [2,14,15], the relation between (CS) and State CS is quite different for pickup and inelastic collective coupling.…”
Section: Evaluating the Dppsmentioning
confidence: 99%
“…[2,14,15], depending on the particular case. In cases where inelastic coupling is included together with reaction channel coupling [2,14,15], the relation between (CS) and State CS is quite different for pickup and inelastic collective coupling. Various relationships have emerged for different cases and to facilitate comparisons, we present values of R CS defined as the ratio of (CS) to State CS.…”
Section: Evaluating the Dppsmentioning
confidence: 99%
See 2 more Smart Citations